Distributed Computing and Internet Technology 5th International Conference, ICDCIT 2008 New Delhi, India, December 10-12, 2008. Proceedings - Parashar, Manish.; Aggarwal, Sanjeev K. (Lecture Notes in Computer Science,, 2009)
This book constitutes the refereed proceedings of the 5th International Conference on Distributed Computing and Internet Technology, ICDCIT 2008, held in New Delhi, India, in December 2008. The 12 revised full papers and 8 revised short papers presented were carefully reviewed and selected from 96 submissions. Featuring current research and results in theory, methodology and applications of Distributed Computing and Internet Technology, the papers are subdivided in topical sections on distributed systems and languages, data grid, security, mobile ad-hoc networks, distributed databases, Web applications, and P2P systems.